Types of Mobile Electronic Support (Individual/Group) and its role in the achievement and development of Speaking and Listening Skills in the English Language Course for intermediate school students - Huraysi, Ali Ahmed; AL- Shehri, Ali Muhmmad (Journal of Educational and Psychological Sciences, 2021)
The aim of the study is to measure the impact of the mobile electronic support types (individual/group) in the achievement and development of speaking and listening skills in the English language course for the intermediate school students, by identifying the types of mobile electronic support (individual/group), and determining the speaking and listening skills in the English language course that must be acquired for intermediate school students. In addition, mobile learning tools and applications can be used in mobile electronic support to develop speaking and listening skills and monitor the role of the electronic support style in developing speaking and listening skills, and measure the impact of the different mobile electronic support types (individual/group) in developing speaking and listening skills. The researcher used the semi- experimental approach method, and a sample consisted of (30 students) of the second intermediate grade students in Al- Andalus National Schools in Jeddah. To achieve the objectives of the study, a learning test and an observation card were built. The results of the research found a positive impact on the effectiveness of the mobile electronic support types (individual/group) in the achievement and development of of speaking and listening skills in English course for intermediate school students. The results revealed that there were statistically significant differences between the mean scores of students in the pre and post- test in the achievement test and Not card of both Mobile E- support types (individual/group) to develop speaking and listening skills in favor of the post- test. The arithmetic mean of the experimental group students of the individual mobile electronic support type in the post application of the observation card for the speaking skill is equal to ( 9.46), and the arithmetic mean of the experimental group students of the group mobile electronic support type in the post application of the observation card for the speaking skill equals (8.01), and the value (T) equals (9.32). The average score of the observation card for the speaking skill of the experimental group students of the (group) mobile electronic support type in the pre- application is (3.09) and in the post- application is (8.01). In light of the results, the research presented several recommendations, including the necessity of applying the group mobile electronic support type in order to increase the speaking and listening skills in the English language course for intermediate school students.